Primaquine in Plasma and Methemoglobinemia in Patients with Malaria Due to Plasmodium vivax in the Brazilian Amazon Basin - Vieira, José Luiz (Am J Trop Med Hyg, 2017)
Primaquine is the only licensed drug available for the elimination of Plasmodium vivax hypnozoites. Methemoglobinemia is currently reported in the course of treatment. There is evidence that metabolites of primaquine formed by the cytochrome pathway are responsible for methemoglobin formation; a genetic polymorphism of cytochrome isoforms; and a potential influence of gender in the activities of these enzymes requiring the establishment of dose × response curves profiles in different population groups. Concentrations of primaquine in plasma and methemoglobin levels were investigated in 54 patients with malaria due to P. vivax during the course of the standard regimen of chloroquine with primaquine (0.25 mg/kg/day for 14 days). All study subjects lived in an endemic area of the Brazilian Amazon Basin. The blood samples were collected before initiation of treatment and 3 hours (range 2–4 hours) after the administration of antimalarial drugs on days 2, 7, and 14. Plasma primaquine concentrations were similar in both genders (males: range = 164–191 ng/mL, females: range = 193–212 ng/mL). Methemoglobin levels ranged from 3.3% to 5.9% in males and from 3.1% to 6.5% in females. There were no significant correlations between the plasma primaquine concentrations or total dose and methemoglobin levels, suggesting that unidentified metabolites rather than parent drug were likely responsible for changes in methemoglobin levels. There was no significant influence of gender on primaquine concentrations in plasma or methemoglobin levels.